Inheritance of Arabica Coffee Resistance to Radopholus similisCobb. - Retno Hulupi; Nasrullah .; Soemartono . (Indonesian Coffee and Cocoa Research Institute, 2007)
A research to get inheritance of Arabica coffee resistance to Radopholus similisnematode was done in screen house and laboratory of Indonesian Coffee and Cocoa Research Institute, also at endemic area of coffee plantation, using F1, F1 R and F2 crossing between BP 542 A(resistant) x Andungsari 1 (susceptible) with their reciprocal, and BP 542 A x Kartika 1. The purpose of this study that was conducted at seedling stage is to formulate a Strategy for Arabica coffee breeding to get resistant varieties to nematode. As the variables of resistance were weight of seedling biomass, percent of root weight deviation, number of root nematodes, number of soil nematodes, reproduction and percent of necrotic root. Using discriminant analysis and fastclus, those data variables were analyzed for genetic of resistance with Statistical Analysis System programme version 8. Genetic study on the inheritance of resistance to R. similiswas started with evaluation of homozigosity of BP 542 A was resistant parent. The result showed that BP 542 A was heterozygous. Therefore, segregation test could not be suggested with segregation pattern principals as Mendel proposed. Segregation test on BP 542 A showed that it was heterozygote and the resistance was controlled by single gene with complete dominant effect, so the progeny segregated in 75% resistant and 25% susceptible. The result of the test showed the absence of maternal effect for root weight deviation and percentage of necrotic root variables, which meant that no cytoplasmic inheritance was involved. Based on the test of segregation ratio, almost all of the resistance was not appropriate for monogenic and or digenic segregation pattern as expected due to non allelic gene interaction that caused epistasis. Key words: Inheritance, resistance, Arabica coffee, Radopholus similis.